2017
DOI: 10.5812/semj.45231
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Group Counseling Based on Cognitive-Behavioral Approach on Pregnancy-Specific Stress and Anxiety

Abstract: Background: Females encounter various stresses during life. Different courses of female's life, namely menstruation, pregnancy, and childbirth, cause particular physical and mental changes that make them more vulnerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The results of the study showed that CBT-based counseling reduced maternal stress and anxiety in the intervention group. However, the mean scores of stress and anxiety between the two groups were statistically significant (27). Their results are also consistent with those of the present study; however, the content and approach of counseling and the counseling method in their research were different from those of the present study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of the study showed that CBT-based counseling reduced maternal stress and anxiety in the intervention group. However, the mean scores of stress and anxiety between the two groups were statistically significant (27). Their results are also consistent with those of the present study; however, the content and approach of counseling and the counseling method in their research were different from those of the present study.…”
Section: Discussionsupporting
confidence: 87%
“…In his study, women were screened in terms of PTSD before the study, but in our study, the women were not screened (26). Seyed Kaboli et al (27) conducted a randomized clinical trial to investigate the effect of group counseling based on CBT on pregnancyspecific anxiety and stress in 62 pregnant women in Karaj. The results of the study showed that CBT-based counseling reduced maternal stress and anxiety in the intervention group.…”
Section: Discussionmentioning
confidence: 95%
“…Pregnancy and childbirth are events that change a woman's worldview and affect her health, emotions, and social roles [35]. Fear is a normal emotion that can be an appropriate response to danger or threat [36].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature and clinical experience, psychological counseling should also focus on the exploration of ambivalent and negative emotions that can develop regarding pregnancy and which can be normal in these circumstances. The evaluation and empowerment of coping strategies can help women cope with difficult situations ( Florsheim et al, 2012 ; Kaboli et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%